parastic infection associated with acute appendicitis in surgically removed appendices - Hassan, Abdul-Razak S.; Mohamed, Ahmed J.; Numan, Nadhim G. (Journal of the Faculty of Medicine Baghdad, 2009)
BACKGROUND-to explor the infections associated with acute appendicitis in surgically removed appendices in Diyala.Materials and Methods: this study include 160 surgically removed appendices with acute appendicitis . the patients were 66 fenales and 94 males. the age range was 5-53years with mean age 22.9±7.2 years.the surgically removed appendicitis were submitted for gross inspection and microscopic examination including direct mount, sedimentation and flotation techniques. Additionally specimens from 25 appendices were processed and examined histopathologically.Results: The rate of parasitic infection in surgically removed appendices was 26.2%. the rate of single parastic infection was 23.1%, while the rate of two parasticwas 3,1%. there were insignificant differences in the rate of infection regarding the sex and age of patients . Additionally there were significant differences in the histopathological changes observed in appendices with parastic infection compared to those without infection.conclusion: parastic infection may play a role in the development of acute appendicitis in patients with surgically removed appendices in Diyala province